Characterization and Exergy Analysis of Triphenyl Borate - Acarali, Nil Baran (CHEM SOC PAKISTAN, 2015)
In this study, unlike from the literature, boron oxide, borax decahydrate, boric acid and borax pentahydrate as boron sources were used to synthesize Triphenyl Borate (TPB). The reactions of TPB were carried out by using both phenol and various boron sources in inert water-immiscible organic solvent successfully. On the basis of analyzes (FT-IR, SEM, TGA/DSC) obtained, it was seen that phenol acted as a support to borate structure framework and thermal characterisation of the amorphous solid under determined conditions suggested that usage of different boron sources had effects for glass transition temperature in TPB production. The exergy analysis was performed to the TPB production to determine efficiency. The exergy analysis showed that the highest exergy efficiency was obtained by using boron oxide as a boron source. Consequently, all analyses results showed that TPB was produced successfully. Accordingly, characterization and exergy analysis supported each other.
Keywords: Triphenyl Borate; Borate; Borax; Exergy; THERMAL-ANALYSIS; BORIC-ACID; CRYSTALLIZATION; MANNITOL; BORON; Chemistry